Food security and dietary patterns in the Tajik Pamirs - Dörre, Andrei (ERDKUNDE, 2024)
For mountain regions in the so-called ‘developing world’, an increase in the number of people considered vulnerable to food insecurity has been noted since the turn of the millennium. Challenging environmental settings, as well as difficult societal conditions have been identified as sources of aggravation to mountain food systems. This paper applies a case study approach, conducted in a remote settlement in the Western Pamirs of Tajikistan, to underpin these general insights with detailed accounts of the complexity of the subject under study, and examines the question of how food security plays out in a specific local setting. The goal is to illustrate how socio-ecological conditions influence the food situation in a specific location, how different parameters generate unequal access to food and effect the nutrition patterns of local households, and what dynamics these patterns exhibit over time. Empirical material was analyzed using Cannon’s food systems approach. The findings exemplify how ensuring food security is made more difficult by the concurrence of challenging conditions, that there is a relationship between the socio-economic status and the dietary patterns of individual households, and how consumption patterns are subject to fluctuations over time. Based upon this, I argue that customized strategies are vital in order to tackle food security challenges in specific settings effectively, and that differentiated, empirically grounded analyses are essential to developing such approaches.